CONSIDERATIONS FOR ENGLISH WRITING IN THE ‘SUPER-DIVERSITY’ OF MULTILINGUAL SOCIETIES - Lesley Harbon (Universitas Negeri Padang, 2016)
In this paper I consider English writing in the context of what Vertovec calls the “super-diversity” (1024) of multilingual societies. First I discuss the characteristics of multilingual societies, and the example of Indonesia as a multilingual society with Bahasa Indonesia, the national language, many regional languages, and languages of the different discourse communities, such as the language used by socially connected young learners. Second I take up the concept of Vertovec’s “super-diversity” (1024), and how it might be applied to Indonesia today. Third I discuss general notions relating to English writing, and particularly the sociocultural theory that has gained good ground in conceptualisations of how best to teach and learn languages over recent decades (Vygotsky). Finally I discuss my own practice in working with university students’ writing through examples of two particular cases. Salient aspects of my work with these two students are shared in the hope of illuminating strategies which may be useful for teachers of English writing in Indonesia.